2006
DOI: 10.1007/s00442-005-0328-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybridization of the Quercus crassifolia×Quercus crassipes complex on the community structure of endophagous insects

Abstract: In a previous study, we showed that the geographic proximity of hybrid plants to the allopatric areas of parental species increases their morphological and genetic similarity with them. In the present work, we explored whether the endophagous fauna of hybrid plants show the same pattern. We studied the canopy species richness, diversity and composition of leaf-mining moths (Lepidoptera: Tischeridae, Citheraniidae) and gall-forming wasps (Hymenoptera: Cynipidae) associated with two species of red oaks (Quercus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 55 publications
2
39
1
Order By: Relevance
“…These zones are also suggested by the Q. crassifolia × Q. crassipes complex (TovarSánchez & Oyama 2004) in which three gall morphotypes were exclusively associated with the hybrid individuals found there (Tovar-Sánchez & Oyama 2006). However, this pattern cannot be generalized, since in another hybrid complex formed by Q. affinis × Q. laurina (González-Rodríguez et al 2004, only one gall morphotype was found in each of the species in this study (see Table 1).…”
Section: Gall Diversity On Mexican Oakssupporting
confidence: 63%
“…These zones are also suggested by the Q. crassifolia × Q. crassipes complex (TovarSánchez & Oyama 2004) in which three gall morphotypes were exclusively associated with the hybrid individuals found there (Tovar-Sánchez & Oyama 2006). However, this pattern cannot be generalized, since in another hybrid complex formed by Q. affinis × Q. laurina (González-Rodríguez et al 2004, only one gall morphotype was found in each of the species in this study (see Table 1).…”
Section: Gall Diversity On Mexican Oakssupporting
confidence: 63%
“…For example, Shuster et al (see Tables 1 and 2 in Shuster et al, 2006) found that 57% of community phenotype variation was due to the genetic differences among genotypes within either pure P. fremontii or P. angustifolia, which was 3 Â greater than community variation between these two species and their hybrids (19%). Moreover, many community metrics scale across the plant taxonomic hierarchy at large geographic scales from genera to the species level (e.g., genera: Brändle and Brandl, 2006;hybrids: Wimp et al, 2004;Tovar-Sánchez and Oyama, 2006;Bangert et al, 2006b;species: Whitham et al, 2006). Thus, genetic scaling has been detected in both phylogenetic and spatial analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in five different systems found that plots with the highest plant genetic diversity supported significantly greater invertebrate species richness than plots with low genetic diversity in both hybridizing and single species systems (Wimp et al, 2004;Reusch et al, 2005;Crutsinger et al, 2006;Johnson et al, 2006;Tovar-Sánchez and Oyama, 2006). Moreover, analyses of arthropod communities in the wild and in common gardens show that many arthropod species are tree genotype dependent (McIntyre and Wimp et al, 2005).…”
Section: Conservation and Genetic Scalingmentioning
confidence: 99%
See 2 more Smart Citations